A Highly Selective 8th Order Band-Pass Filter for Lightning Remote Sensing Applications - AL-SHAIKHLI, TAHA RAAD; AL-SAEEDI, MUSTAFA MURTDHA; HAMZAH, ABDULNISER KHALD; AHMAD, MOHD RIDUAN; AHMAD, BADRUL HISHAM; AL-TIMARI, USAMA S. (The journal of contemporary issues in business and government, 2021)
Recently, it has been discovered there was an emission of microwave radiation in advance of the lightning process. Therefore, a lot of researches focus on designing alarm systems that can detect and analyze these radiated signals. The previous designs based on commercial band-pass filters which have low accuracy factor and quite expensive as well as the detected signal were tiny in amplitude, thus higher efficiency filters are needed with a flat frequency response for passed band frequencies between 950 MHz to 1050 MHz in order to avoid the GSM band which generates a high interference to the mentioned detection system. In this research, a band-pass filter has been designed and tested for measurement with a center frequency of 1 GHz and by using Advance Design System (ADS) to be simulated and then fabricated on FR-4 substrate. The measurement came with good compatibility to the simulation results at return loss of -34.747 dB and also the insertion loss of -3.83 dB. This design also works perfectly for the Lightning detection sensor of Narrow Bipolar Event (NBE).